2008 20th International Conference on Indium Phosphide and Related Materials 2008
DOI: 10.1109/iciprm.2008.4702897
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of compound semiconductors with low dislocation densities

Abstract: This paper will highlight some technological developments in the field of Vertical Gradient Freeze growth of InP and GaAs for providing substrates with low dislocation densities. Furthermore, the role of micropipes and basal plane dislocations during sublimation and epitaxial growth of SiC will be addressed. Finally, different strategies will be illustrated to achieve GaN with high structural perfection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In general, grain boundaries can limit the optoelectronic properties of materials due to a high density of dangling bonds and impurity segregation caused by differences in diffusion behavior as compared to the bulk material. Analyzing our TF-VLS p -InP via a combination of secondary ion mass spectroscopy (SIMS) and capacitance–voltage (CV) profiling revealed that only ∼10% of the incorporated Zn was electrically active in our TF-VLS p -InP, leading to the possibility that much of the interstitial Zn accumulates at the interfaces and along grain boundaries . Moreover, the bulk material quality of single crystal InP can differ from thin-film InP as well, which is caused by structural differences inherent to the growth process such as dislocations, twin boundaries, and related defects …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, grain boundaries can limit the optoelectronic properties of materials due to a high density of dangling bonds and impurity segregation caused by differences in diffusion behavior as compared to the bulk material. Analyzing our TF-VLS p -InP via a combination of secondary ion mass spectroscopy (SIMS) and capacitance–voltage (CV) profiling revealed that only ∼10% of the incorporated Zn was electrically active in our TF-VLS p -InP, leading to the possibility that much of the interstitial Zn accumulates at the interfaces and along grain boundaries . Moreover, the bulk material quality of single crystal InP can differ from thin-film InP as well, which is caused by structural differences inherent to the growth process such as dislocations, twin boundaries, and related defects …”
Section: Introductionmentioning
confidence: 99%
“…8 Moreover, the bulk material quality of single crystal InP can differ from thin-film InP as well, which is caused by structural differences inherent to the growth process such as dislocations, twin boundaries and related defects. 13 Hydrogen in semiconductors can play an important role by modifying the electrical properties of the material. It does so by passivating native defects and impurities, or inducing electrically active defects.…”
Section: Introductionmentioning
confidence: 99%